2011
DOI: 10.1007/s10393-011-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Influenza A Viruses in Wild Birds in Southern Africa

Abstract: Avian influenza viruses (AIVs) are pathogens of global concern, but there has been little previous research on avian influenza in southern Africa and almost nothing is known about the dynamics of AIVs in the region. We counted, captured and sampled birds regularly at five sites, two in South Africa (Barberspan and Strandfontein) and one in each of Botswana (Lake Ngami), Mozambique (Lake Chuali) and Zimbabwe (Lakes Manyame and Chivero) between March 2007 and May 2009. The South African and Zimbabwean sites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 25 publications
4
57
0
Order By: Relevance
“…Bird counts in each counting site were implemented as described previously (Caron et al, 2010;Cumming et al, 2011b). Focal counts were undertaken to estimate species diversity and the abundance of waterfowl and domestic communities.…”
Section: Bird Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird counts in each counting site were implemented as described previously (Caron et al, 2010;Cumming et al, 2011b). Focal counts were undertaken to estimate species diversity and the abundance of waterfowl and domestic communities.…”
Section: Bird Countsmentioning
confidence: 99%
“…At the local scale considered in our study, the ability of a potential "bridge" individual to link any pair of compartments is assumed not to vary greatly among bridge candidates. This assumption may be challenged for some species but: 1) capture-recapture of wild birds in the study site demonstrated that individuals of multiple species could be at opposite locations of the study site along the lake shores (Cumming et al, 2011a;Chiweshe and Caron, 2012); 2) many bird species in southern Africa adopt a seasonal nomadic behaviour leading to a scale of movements far superior to the scale of the study site considered here (hundreds of kilometres vs. a few kilometres respectively).…”
Section: Estimation Of the Rate Of Host Contact Between Compartmentsmentioning
confidence: 99%
“…Standard approaches for predicting species occurrences (Cumming 2007a;Elith and Graham 2009; do not necessarily translate well into a landscape epidemiology context to predict pathogen occurrences because of the additional complexities involved in having an animal, rather than a biophysical habitat, as the pathogen's habitat. In Southern Africa, for example, Cumming et al (2011) found no clear annual pattern of AIV prevalence in waterfowl and explained this as a consequence of the dynamic nature of wetland resources and the flexibility of waterfowl movement strategies (Caron et al 2011;Cumming et al 2011Cumming et al , 2012b. In a sample of Afrotropical wetlands that included data from East and West Africa as well as Southern Africa, showed that although variation in AIV prevalence was related to waterfowl density and the arrival of European migrants, it was not influenced by regional climatic conditions.…”
Section: Interactions Between Environmental Factors and Aiv Prevalencementioning
confidence: 99%
“…Although health is considered a component of well-being (Millennium Ecosystem Assessment (MA) 2003), there are very few examples within the resilience literature focused specifically on health (Berkes et al 2012). Thus, there is little guidance in dealing with specific health issues save counted exceptions such as Janssen and Martens (1997), Cumming (2010), andCumming et al (2011). Here is where an approach to health that is rooted in systems thinking but that emphasizes equity, participation, and knowledge-toaction can be useful for resilience thinkers wishing to be more explicit and empirical in their treatment of well-being and health and move from theory to practice.…”
Section: Why the Link Between Ecohealth And Resilience?mentioning
confidence: 99%